Progesterone and plasma metabolites in women with and in those without premenstrual dysphoric disorder. Issue 12 (5th September 2018) - Di Florio, Arianna; Alexander, Danny; Schmidt, Peter J.; Rubinow, David R.
Abstract : Background: The molecular mechanisms underpinning the progesterone‐triggering mood symptoms in women with premenstrual dysphoric disorder (PMDD) are unknown. Cell metabolism is a potential source of variability. Very little is known about the effect of progesterone sensitivity on the metabolome. In this study, we aimed to characterize the effects of progesterone on the global metabolic profile and explore the differences between women with PMDD and controls. Methods: Plasma was obtained from 12 women with prospectively confirmed PMDD and 25 controls under two hormone conditions: (1) gonadal suppression induced by leuprolide acetate (3.75 mg IM monthly) and (2) add‐back phase with leuprolide and progesterone (200 mg twice daily by vaginal suppository). The global metabolic profile was obtained using liquid and gas chromatography followed by mass spectrometry. Differences between groups and time points were tested using repeated measures analysis of variance. The false discovery rate was calculated to account for multiple testing. Results: Amino acids and their derivatives represented 78% (28/36) of the known compounds that were found in significantly lower plasma concentrations after progesterone administration than during gonadal suppression. The concentration of tyrosine was nominally significantly decreased after progesterone add‐back in controls, but not in cases ( P  = 0.02). Conclusion: Plasma levels of some amino acids are decreased in response to progesterone. Albeit preliminary, evidence further suggests that progesterone has a different effect on the metabolic profiles of women with PMDD compared to controls. Further research is needed to replicate our findings in a larger sample and to identify the unknown compounds, especially those differentially expressed.